2009
DOI: 10.1002/pi.2631
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II) and nickel(II) complexes bearing mono(imino)pyridyl and bis(imino)pyridyl ligands: preparation, structure and ethylene polymerization/oligomerization behaviors

Abstract: BACKGROUND: Ethylene oligomerization is the major industrial process to produce linear α‐olefins. Recently much work has been devoted to late transition metal catalysts used in this process, especially those with 2,6‐bis(imino)pyridyl dihalide ligands. Considering that most work has focused on simple modification to the substituents in imino‐aryl rings based on the symmetric bis(imino)pyridyl framework, here we expand this work to the asymmetric mono(imino)pyridyl ligands. RESULTS: The preparation, structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Butene-1 was the only detectable product of this reaction, and no traces of solid polymer were found. Such reaction behavior is similar to that reported for bis(imino)pyridine-based and structurally related nickel(II) complexes with N,N,N-donor ligands. …”
Section: Resultssupporting
confidence: 85%
“…Butene-1 was the only detectable product of this reaction, and no traces of solid polymer were found. Such reaction behavior is similar to that reported for bis(imino)pyridine-based and structurally related nickel(II) complexes with N,N,N-donor ligands. …”
Section: Resultssupporting
confidence: 85%
“…The activity increases sharply when the temperature rises from 80 °C (1.177×10 4 g mol −1 ⋅ h −1 ) to 110 °C (1.604×10 4 g mol −1 ⋅ h −1 ), and then decreases as the temperature continues to rise to 120 °C (1.334×10 4 g mol −1 ⋅ h −1 ). A low temperature is unfavorable probably because it hinders the formation of active species, but too high a temperature may cause a decrease of MMA solubility and deactivation of catalyst [26–28] . All the resulting PMMA had high molecular weights of around 10 5 g mol −1 with narrow molecular weight distributions (dispersity indices [PDI]: 1.72∼2.73) in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of mono(imino)pyrrole ligands were developed, nearly all of the reported ligands bore H side arms [10][11][12][13][14][15][16]. We have expanded this work to mono(imino) pyrrole ligands with a -CH 3 side arm in order to have greater electronic and steric effects.…”
Section: Introductionmentioning
confidence: 99%
“…Bis(imino)pyridyl-metal catalysts have been an attractive research field because of their flexible structural modifications and complexation between ligand and metal, as well as outstanding catalytic performance. Studies have mainly concentrated on adjusting the structure of the ligand, usually using the following ways [5][6][7][8]: (1) introducing heteroatoms to the pyridine ring to get an N-based sixmembered heterocyclic imino ligand, such as pyrimidine, pyrazine, and triazine ligands; (2) replacing the six-membered heterocycle with a five-membered heterocycle such as a pyrrole, thiophene, or furan ring; (3) modifying the imino substituent to get ligands with different side arms, such as carbazole or Pybox ligands [9]; or (4) changing the symmetric bis (imino) structure to an asymmetric structure [10][11][12][13]. For example, zirconium and titanium complexes bearing mono(imino)pyrrole ligands, reported by Fujita [14,15] and Bochmann et al [7], were demonstrated to be good catalysts for ethylene polymerization.…”
Section: Introductionmentioning
confidence: 99%